PENERAPAN MANAJEMEN KELAS PADA PEMBELAJARAN DONGENG UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS II SDN JADI IV SEMANDING TUBAN - Sumarmi Sumarmi (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
This study was arranged based on a qualitative descriptive research design which the results of this study indicate that the application of classroom management in fairy tale learning to improve learning motivation of students in class II SDN Becomes IV Semanding Tuban has not been maximized. The results showed that the fairy tale learning process had not been optimal for the application of classroom management because the teacher had not made a classroom management plan before the learning took place and the lack of learning facilities in the classroom so that the class was less conducive. Class management emphasizes efforts to achieve student learning motivation and student achievement, so that visible classroom management is a systematic and structured management process by prioritizing strategic planning consisting of class management design in fairy tale learning, classroom management in fairy tale learning and assessment in learning fairy tales so as to increase student learning motivation.